University-based Approaches for Older Adults : Adapting Universities for the 100-year Lifespan - McGill Community For Lifelong Learning (MCLL) (2020)
This study, University-Based Approaches for Older Adults: Adapting Universities for the 100-year Lifespan, uses the McGill Community for Lifelong Learning (MCLL) as a case study to probe issues related to seniors’ learning within university contexts, including demographics, effects of learning on the lives of older adults, mutual benefits and expectations for learners and the university community of which they are members. The intention of this research is to enable the continuous improvement of MCLL and, given national and international demographic shifts, to add new perspectives to the literature on the increasingly vital topic of continuing to learn throughout the lifespan.

McGill Community For Lifelong Learning : Fall 2021 - McGill Community For Lifelong Learning (MCLL) (2021)

April 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 9

December 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 12

June 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 10

May 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 7

Spring 2023 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 8